Ethnicity and risk for SARS-CoV-2 infection among the healthcare workforce: Results of a retrospective cohort study in rural United Kingdom - Maxime Inghels; Ros Kane; Priya Lall; David Nelson; Agnes Nanyonjo; Zahid Asghar; Derek Ward; Tracy McCranor; Tony Kavanagh; Todd Hogue; Jaspreet Phull; Frank Tanser (International Journal of Infectious Diseases, 2022)
Background: The reason why Black and South Asian healthcare workers are at a higher risk for SARS-CoV-2 infection remain unclear. We aimed to quantify the risk for SARS-CoV-2 infection among healthcare staff who belong to the ethnic minority and elucidate pathways of infection. Methods: A one-year follow-up retrospective cohort study has been conducted among National Health Service employees who were working at 123 facilities in Lincolnshire, UK. Results: Overall, 13,366 professionals were included. SARS-CoV-2 incidence per person-year was 5.2% (95% CI: 3.6–7.6%) during the first COVID-19 wave (January–August 2020) and 17.2% (13.5–22.0%) during the second wave (September 2020–February 2021). Compared with White staff, Black and South Asian employees were at higher risk for SARS-CoV-2 infection during both the first wave (hazard ratio, HR 1.58 [0.91–2.75] and 1.69 [1.07–2.66], respectively) and the second wave (HR 2.09 [1.57–2.76] and 1.46 [1.24–1.71]). Higher risk for SARS-CoV-2 infection persisted even after controlling for age, sex, pay grade, residence environment, type of work, and time exposure at work. Higher adjusted risk for SARS-CoV-2 infection were also found among lower-paid health professionals. Conclusion: Black and South Asian health workers continue to be at higher risk for SARS-CoV-2 infection than their White counterparts. Urgent interventions are required to reduce SARS-CoV-2 infection in these ethnic groups.